PENGARUH CURRENT RATIO (CR), TOTAL ASSET TURNOVER (TATO), PERTUMBUHAN PERUSAHAAN, KEBIJAKAN DIVIDEN, DAN UKURAN PERUSAHAAN (SIZE) TERHADAP NILAI PERUSAHAAN: (Studi pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di BEI periode 2017-2018) - Ulfah , Maria (Program Studi Manajemen Bisnis Syariah STAIN Mandailing Natal, 2020)
The purpose of this research was conducted to determine the significance of the effect of current ratio (cr), total asset turnover (tato), growth, dividend policy, and size firm to the value of the company at manufacturing company in Indonesia Stock Exchange 2017-2018. Based on 18 companies, selection of the sample is determinde of the purpose sampling methode and predetermined criteria. Sources of data in this research is secondary data which is derived from BEI’s official site (www.idx.co.id). The analytical method used is panel data regression analysis with data processing tools is Eviews 9. The result of this research are tato and dividend policy has positive effect towards value of company. Meanwhile cr, growth, and size firm hasn’t effect towards value of company.